Ultrafiltration membranes for dye wastewater treatment: Utilizing cellulose acetate and microcrystalline cellulose fillers from Ceiba Pentandra - Abdullah, Romario; Astira, Dinia; Zulfiani, Utari; Rahmad Widyanto, Alvin; Rahmawati, Zeni; Gunawan, Triyanda; Kusumawati, Yuly; Hafiz Dzarfan Othman, Mohd; Fansuri, Hamzah (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Dye hurts the threat of human health problems and environmental pollution. Microcrystalline cellulose (MCC) based membrane is a good material to be used as an dye separation membrane for having the high hydrophilicity of the membrane. It has been successfully isolated from kapok (ceiba pentandra) with characteristic X-ray diffraction patterns and FTIR absorption peaks, which corresponded to the typical peaks of cellulose. The ultrafiltration membrane was made up of a cellulose acetate matrix created using the phase inversion method. Characterization results indicated that the inclusion of MCC derived from kapok led to a reduction in the contact angle from 65 to 52o, and an increase in membrane porosity from 82 to 85%. In the separation of dye, the composite membrane incorporating MCC filler demonstrated superior performance compared to the membrane lacking MCC, manifesting in an elevated water flux from 43 to 84 L/m².h and methylene blue (MB) rejection from 64 to 99%. The use of MCC as a filler in cellulose acetate membranes can enhance the characteristics and performance of the membrane in MB separation.